Mathematical modeling of di-ethyl-hexyl-sebacate nanoparticle formation in a free turbulent jet under high nucleation rate conditions. (June 2016) - Gilfanov, A.K.; Koch, W.; Zaripov, S.K.
Abstract: Mathematical modeling of di-ethyl-hexyl-sebacate (DEHS) nanoparticle formation due to homogeneous nucleation, condensation and coagulation in a hot free turbulent jet issuing into a colder environment is performed. The Reynolds-averaged Navier–Stokes equations are used to describe the fluid flow. The aerosol dynamics is treated by transforming the general dynamic equation into moment equations which are closed by assuming a lognormal shape of the particle size distribution. The contribution of condensation and coagulation to particle formation in the case of high saturation ratios and nucleation rates is studied. The sensitivity of the model to existing approximations of the vapor saturation pressure curve and the ambient temperatures is analyzed. The influence of the main control parameters of the system, such as vapor saturation temperature and nozzle exit velocity, on the aerosol characteristics formed in the turbulent jet is investigated. Highlights: The model of nanoparticle formation in a free turbulent jet using CFD. The initial growth of particles is by condensation even at very high nucleation rate. The parameters of PSD do not depend on the radial coordinate in the free jet. PSD formed mainly by coagulation is least sensitive to external parameters. Knowledge of the influence of saturation temperature and flow rate on feed aerosol.